Using CUBES strategy in a remote setting for primary mathematics word problems - Christina Teo Lian Wan; Nor Azura Abdullah (Jurnal Elemen, 2023)
Various research has been carried out worldwide over the years to identify ideal methods that are helpful to pupils when solving mathematical word problems. This study aims to examine the use of the CUBES Maths Strategy, a mnemonic device, to solve word problems and was conducted in a remote setting. An action research approach using a mixed method research was conducted where all data collected were analysed both quantitatively and qualitatively. The participants involved were pupils from a small local government primary school, aged between 8 and 9. Pupils’ test results from the given pre and post-tests were quantitatively analysed using Wilcoxon Signed-Rank Test, which concluded that there was no significant change in the difference in test scores. Newman’s Error Analysis interview was conducted to investigate the source of errors committed by the pupils, which concluded that the most prominent type of error made is the Comprehension error, followed by the Transformation error. From the observations and reflections, it can be deduced that, as the research was done in a remote setting, the use of the CUBES Maths Strategy was not fully utilised. These results could be based on the interactions between teachers and students during remote online learning.